Social economic conditions of farming community in Salek Jaya Village, Air Saleh District - Aan Afandi; Deni Puji Hartono; Budi Utomo; Mega Kusuma Putri; Helfa Septinar (Universitas Veteran Bangun Nusantara, 2021)
Purpose of this study was to determine and describe the socio-economic conditions of the lowland rice farming community in Salek Jaya Village, Air Saleh District. This study used descriptive qualitative method. This study used 15 community respondents who work as farmers. Collecting data using observation, interview, and documentation techniques. The data analysis technique uses descriptive analysis and is presented in a diagrammatic table. The results of this study indicate that the age of farmers ranges from 40-49 years (53%) including the productive age, the last level of education taken by farmers who graduated from Elementary School (SD) 73%, regarding health facilities according to respondents is feasible (67%) , the social interaction between farmers is well established without any obstacles, the income from farming that is obtained in one planting season is around Rp. 10,000,000 - Rp. 15,000,000 (73%), while the total expenditure of farmers, both for farming capital and for their daily needs, ranges from> Rp. 5,000,000 (20%) and Rp. 600,000 - Rp. 1,000,000 (60%) and the number of dependents as many as 3 people.